2011
DOI: 10.1590/s1517-83822011000200026
|View full text |Cite
|
Sign up to set email alerts
|

Production flush of Agaricus blazei on Brazilian casing layers

Abstract: This study aimed to verify the biological efficiency and production flushes of Agaricus blazei strains on different casing layers during 90 cultivation days. Four casing layers were used: mixture of subsoil and charcoal (VCS), lime schist (LSC), São Paulo peat (SPP) and Santa Catarina peat (SCP); and two genetically distant A. blazei strains. The fungus was grown in composted substratum and, after total colonization, a pasteurized casing layer was added over the substratum, and fructification was induced. Mush… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 2 publications
(2 reference statements)
2
7
0
Order By: Relevance
“…As Colauto et al . reported for two Brazilian cultivars, we observed that changes in mushroom fresh weight during harvest depended on the strain, although all strains except CA643 produced less heavy mushrooms during the d20–d30 period.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…As Colauto et al . reported for two Brazilian cultivars, we observed that changes in mushroom fresh weight during harvest depended on the strain, although all strains except CA643 produced less heavy mushrooms during the d20–d30 period.…”
Section: Discussionsupporting
confidence: 84%
“…The average production in Brazil was estimated to be 8-16% after 120 days of cultivation. 7 As Colauto et al 24 reported for two Brazilian cultivars, we observed that changes in mushroom fresh weight during harvest depended on the strain, although all strains except CA643 produced less heavy mushrooms during the d20-d30 period. As regards the whole harvest, Brazilian strains were generally more interesting than wild European strains for individual fresh weight and dry matter content, but this was offset by the far higher yield of the wild strains.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Moreover, Kerketta et al (2018) uses various casing materials for the growth of milky mushroom and found that casing materials positively affected the growth and yield of mushroom. Casing soil protects the compost against desiccation, supports the mushroom against pests and diseases, provides support for developing sporophores and provides a gaseous exchange for growth and development of mushrooms (Colauto et al, 2011).…”
Section: Experiments 3 Effect Of Different Casing Materials On the Yield And Biological Efficiency Of Milky Mushroommentioning
confidence: 99%
“…It is also appreciated for their sensory characteristics (Escouto et al 2005). However, Colauto et al (2011) report that the proposed names are illegitimate due to previous publishing. Therefore, in this study the name A. blazei is used to this fungus.…”
Section: Introductionmentioning
confidence: 99%